Concurrent Training and the Acute Interference Effect on Strength: Reviewing the Relevant Variables - Panissa, Valéria Leme Gonçalves; Greco, Camila C. [UNESP]; Ribeiro, Natalia; Julio, Ursula F.; Tricoli, Valmor; Franchini, Emerson (Wolters Kluwer, 2022)
This review analyzes relevant variables involved in acute interference effects of concurrent training (CT) sessions of aerobic exercise followed by strength exercises. The aerobic exercise intensity, mode, volume, duration of recovery interval between exercises, muscle groups involved, and utilization of ergogenic aids are the variables identified in this review. High-intensity interval aerobic exercises result in more pronounced negative effects on strength-endurance exercise but not in maximal strength. Cycling results in more negative effects on strength-endurance performance exercise than running. A 4-hour to 8-hour recovery interval seems to be enough to avoid interference on strength-endurance performance. Reduction in strength-endurance performance is located in muscle groups involved in both exercises. Low aerobic exercise volume (3 km) with ∼18 minutes of duration does not diminish strength endurance, whereas higher volumes (5 and 7 km) with ∼30 and ∼42 minutes of duration, respectively, generate impairments. Caffeine, carbohydrate, and beta-alanine are not able to revert the deleterious effect on strength-endurance performance, whereas creatine and capsaicin analog supplementation are. Thus, these variables must be taken into consideration to prescribe and organize a CT session. This information may help coaches to organize exercise sessions that minimize or avoid the impairment in strength performance after aerobic exercises.
Keywords: concurrent exercise; maximum strength; strength endurance